2011
DOI: 10.1002/jrs.2642
|View full text |Cite
|
Sign up to set email alerts
|

On the interpretation of the Raman spectra of Maya Blue: a review on the literature data

Abstract: The Raman spectroscopy of Maya Blue (MB), a nanostructured organic-inorganic hybrid material, has received considerable attention. A re-evaluation of the Raman literature data for indigo dye, genuine MB samples and model specimens obtained by the binding of indigo to phyllosilicate clays, such as palygorskite and sepiolite, using chemometric analysis of normalised spectra is reported. Available data present features in support of the following ideas: (1) dehydroindigo accompanies indigo in MB; (2) different to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 61 publications
5
41
0
Order By: Relevance
“…At 1,668 cm −1 we find a symmetric ν(C=O) mode involving the two carbonyl groups, which is coupled with the ν(C=C) of the central C=C group. This is consistent with the assignment of the experimental band found at 1,701 cm −1 [47,49,50], though other authors [48] found an additional coupling with the δ(CC) of the five-membered ring. An asymmetric ν(C=O) mode of both carbonyl groups that is coupled with δ(NH) is found at 1,623 cm −1 in our calculations.…”
Section: Effect Of Adsorption On Vibrational Frequenciessupporting
confidence: 90%
See 3 more Smart Citations
“…At 1,668 cm −1 we find a symmetric ν(C=O) mode involving the two carbonyl groups, which is coupled with the ν(C=C) of the central C=C group. This is consistent with the assignment of the experimental band found at 1,701 cm −1 [47,49,50], though other authors [48] found an additional coupling with the δ(CC) of the five-membered ring. An asymmetric ν(C=O) mode of both carbonyl groups that is coupled with δ(NH) is found at 1,623 cm −1 in our calculations.…”
Section: Effect Of Adsorption On Vibrational Frequenciessupporting
confidence: 90%
“…A similar frequency shift was observed in the experimental spectrum of indigo sorbed in palygorskite [46][47][48]. However, other authors have assigned the band at 1,623-1,625 cm −1 to C-C and C-H vibrations [49]. Our calculations allow us to assign the band at 884 cm −1 to in-plane bending of the carbonyl group δ(CO).…”
Section: Effect Of Adsorption On Vibrational Frequenciessupporting
confidence: 71%
See 2 more Smart Citations
“…That same year Shepard (1962) and Shepard and Gottlieb (1962) suggested that the pigment was a clayeorganic complex, and indeed, five years later, the remaining component was identified as the organic colorant, indigo (Kleber et al, 1967). Since then, research on Maya Blue has focused on several interrelated themes, and at least two authors have provided lengthy summaries of the Maya Blue research from a chemical and molecular perspective (Doménech et al, 2011;Giustetto et al, 2011).…”
Section: Brief History Of Maya Blue Researchmentioning
confidence: 96%